Evaluación del efecto de aplicación del activador fisiológico orgánico florone en el cultivo de cacao - López Vera, Hugo José (2012)
The present research was carried out on the grounds of the farm "San Pablo", belonging to the Faculty of agricultural sciences, Technical University of Babahoyo, located in the 7.5 Km of track Babahoyo - Montalvo; testing the physiological Activator organic Florone in cocoa clones ' 548´ and ' 64´; (in order: to) study the agronomic behaviour and performance of clones in the presence of the trip; (b) identified the dose appropriate implementation of the enabler to increase the yield of cocoa; (and c) economic analysis of treatments. The treatments were composed of combinations of clones with doses of the Activator. The doses were: 0.30; 0.45 and 0.60 l / has of Florone; We also included two witness, the one without activator and one without activator and fertilize: giving a total of 10 treatments.........